Reinterpretasi Teks Keluaran 20:17 Untuk Memperkuat Pemberantasan Korupsi - Jefrie Walean (Discreet: Journal Didache of Christian Education, 2021)
This study presents an analysis of corrupt behavior from the perspective of the text of Exodus 20:17 and the constitution. This research aims to place the perspective of the Bible and the constitution in parallel. This study uses analytical and descriptive methods to develop thinking patterns related to the linear perspective of the Bible and the constitution as the foundation for the Corruption Eradication Commission and the Bible. This study concludes that the phrase do not covet in the text of output 20:17 is linear with a juridical perspective that coveting other people's legal property is a criminal offense.